Buckling behavior of plastically strained metallic panels - Çimen, Taha (Graduate School, 2025)
During the post-buckling stage, plastic strain can be occurred due to unexpected service loads, which alters the stiffness of the panel and affects their buckling resistance. However, the extent of this reduction and its impact on structural performance have not been thoroughly studied. The objective of this thesis is to investigate the effect of plastic strain on the critical buckling load of panels under in-plane shear loading. To achieve this, both experimental and numerical analyses were conducted. In the experimental study, an AL-1050 alloy square panel with 330 mm side length and 1 mm thickness of was utilized using a picture frame test setup. Two strain gauges were mounted in a back-to-back on the panel to measure both elastic and plastic strains during loading For the numerical study, finite element simulations were performed in Abaqus to evaluate the effect of different levels of plastic strain (25%, 50%, 75% and 100%) on the secondary buckling load. These plastic strain levels were taken from the post-buckling condition at the ultimate buckling load, and used as predefined inputs to recalculate the buckling loads. A total of 18 panel models were created using AL-5754 and ST-37 materials for the numerical study. For each material, panels were modelled with side lengths of 500 mm, 750 mm, and 1000 mm, and thicknesses of 2 mm, 3 mm, and 4 mm. The aim of the study is to compare the initial critical buckling loads with the secondary buckling loads calculated under different levels of plastic strain, and to identify a relationship between the reduction percentage and the dimension of the panel. The findings contribute to a deeper understanding of buckling behavior in plastically strained metallic panels and provide important insights for the design and safety of load-bearing structures in engineering applications.
Plastik gerinime uğramış metal panellerin burkulma davranışı
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2025
Keywords: buckling behavior; burkulma davranışı; finite element method; sonlu elemanlar yöntemi